Effects of the intervention of the Multicenter Study IDEFICS on the prevalence of caries in Spanish children - Vinícius Aguiar Lages; Maria Paula Rando Meirelles; Marília Jesus Batista; Carolina Matteussi Lino; Andréa Moscardini da Costa; Luis Alberto Moreno Aznar; Maria da Luz Rosário de Sousa (Universidade Estadual de Campinas, 2021)
Aim: To evaluate the effects of an intervention for the prevention of obesity on the prevalence of dental caries disease in Spanish children. Methods: Two cities participated intervention study nested in a cohort IDEFICS (Identification and prevention of dietary and lifestyle induced health effects in children and infants): Huesca, where there was a 2-year intervention, which encouraged less sugar consumption; and Zaragoza (control). The prevalence of caries was evaluated by examining the 1st permanent molars in the 7-11 age range, using the ICDAS (International Caries Detection and Assessment System). These teeth erupt at 6 years of age and at the baseline (2007-2008) were free of caries because they were not present in the oral cavity. As outcomes, white spots were selected, combining the ICDAS criteria 1 and 2, and untreated caries, combining criteria 4, 5 and 6. Their association with socioeconomic variables, BMI (Body Mass Index), frequency of sugar intake, sex and parents' perceptions of their children, was investigated. To do so, the chi-square test was applied (p<0.05). Results: The sample consisted of 281 children. The prevalence of white spots and untreated caries was higher in Huesca, despite the intervention. There was no association between the outcomes and the variables studied (p>0.05). Conclusion: The intervention for the prevention of obesity did not exert any association with the prevalence of caries in Spanish children.